Whither CRM?—30 years on: a narrative review and position paper on the future of aviation CRM training - Pollitt, Alex; Vlaskamp, Daan; Blundell, James; Landman, Annemarie (MDPI, 2026)
For almost fifty years, Crew Resource Management (CRM) has been a cornerstone of aviation safety and training. This narrative review examines the current state of CRM training and identifies key directions for future development, including the integration of artificial intelligence, increasing attention on mental health and resilience, and workforce diversity. While there is evidence of gradual evolution in CRM practices, reflected in updated regulatory frameworks, competency-based approaches, and a growing community of human factors and aviation psychology specialists, progress remains uneven across the industry. We argue that many aviation operators and training organizations still lack robust institutional mechanisms to systematically translate emerging scientific evidence into training design and delivery. As a result, advances in research on teaching and learning methods and human performance are not consistently brought forward into everyday training practices. The review concludes with a set of practical recommendations aimed at strengthening knowledge exchange between researchers and operational stakeholders, enhancing evidence-informed training, and supporting the modernization of CRM in a rapidly changing operational environment.
This article belongs to the Special Issue Human Factors and Performance in Aviation Safety
Keywords: 40 Engineering; 3 Good Health and Well Being; 4001 Aerospace engineering; Crew Resource Management; aviation human factors; aviation training; Evidence-Based Training; training design; non-technical skills; aviation psychology; Threat and Error Management; competency-based training and assessment